Synergistic effect of climatic and non-climatic factors on food security in Syria: an autoregressive distributed lag approach - Naji AlFraj (Development Studies Research)
Food security has always been the main goal of Syrian agricultural strategy. Therefore, the main objective of this study is to examine the dynamic relationship between selected climatic and non-climatic variables and food security in Syria from 1961 to 2018. The autoregressive distributed lag (ARDL) bounds testing approach is applied to estimate the association among the study variables with evidence of long-run and short-run analysis. The long-run estimates revealed that non-climatic variables including crop production, agricultural land, land under cereal production, and population, positively affected food security. Moreover, climatic variables including temperature and CO2 emissions positively affected food security in the long-run. The findings revealed that in the short-run, fertilizer affected food security positively. However, in the long run, the effect of fertilizer consumption turned out to be negative and significant. This study suggests that governments may consider measures to improve food security in Syria. Governments should focus on the issue of using climate-adapted plant varieties. Increasing the area under cereal crops and reducing agricultural land degradation could be an important long-term strategy for the government. There is a need to properly train farmers regarding fertilizer usage and switch from chemical fertilizer to organic fertilizer.